Overruling Crawford v. Washington: Why and How - Crump, David (2012)
The article discusses a court case in which decision of Roberts Court on Confrontation Clause was overruled by the Crawford Court. It states that Confrontation Clause provides the right of vigorous cross-examination, right to face-to-face presentation of witnesses and the right to severance to the criminal defendant. It highlights several Payne-Parenthood factors supporting the overruling of Crawford including fewer disturbances in reliance interests, dissenting justices and judicial fudging